THE INFLUENCE OF TRAINING QUALITY AND ORGANIZATIONAL SUPPORT ON THE COMPETENCE OF PROSPECTIVE FUTURES BROKER REPRESENTATIVES THROUGH THE EXISTENCE OF PROFESSIONAL CERTIFICATION INSTITUTIONS IN THE FIELD OF COMMODITY FUTURES TRADING - Asep Irvan Nurohim; Zulkifli Rangkuti; Hadi Purnomo (Yayasan Pendidikan Cahaya Budaya Indonesia, 2026)
This study aims to analyze the influence of training quality and organizational support on the competence of prospective futures broker representatives through the existence of a Professional Certification Institute (LSP) in the field of commodity futures trading. The problem in this study is motivated by the importance of improving human resource competence in facing the increasingly competitive commodity futures trading industry and the need for professionals with competency certification according to industry standards. The research method used is a quantitative method with a descriptive and verification approach. Data collection was conducted by distributing questionnaires to prospective futures broker representatives who participated in the training and competency certification program. Data analysis techniques used multiple linear regression analysis and path analysis to determine the direct and indirect effects between research variables. The results of the study indicate that the quality of training and organizational support have a positive and significant effect on the competence of prospective futures broker representatives. In addition, the existence of a Professional Certification Institute has been proven to strengthen the relationship between training quality and organizational support on improving participant competence. The implications of this study are expected to be considered by training institutions, brokerage firms, and regulators in improving the quality of human resource development through training and competency certification that meets national standards.